Prikaz medicinske, javnozdravstvene in slovenske zgodovine tuberkuloze - Jaunig, Senta (Medicinski razgledi, 2012)
This review deals with the history of tuberculosis from the medical and social perspectives. It presents tubereulosis as an old disease with traces of it found on the human body as far back as prehistorie times, whieh spread the most with industrialization. For this so-called white plague, medicine did not have an effective eure until the 20th century. The earliest relatively successful curative methods for tuberculosis treatment were isolation, rest eure, climatotherapy, dietotherapy and moral support of tuberculosis patients. They were treated in sanatoriums, which were accessible only to wealthy patients. With Robert Koch's discovery of the tuberculosis pathogen in 1882, there were substantial developments in medicine and subsequently also several revolutionary changes as attempts were made to develop avaccine. The public health aspect of fighting tuberculosis with dispensary and educational programmes already led to major successes between World War I and II. After the introduction of streptomycin in tuberculosis treatment after World War II, it seemed that medicine had finally won the battle with tuberculosis. At the same time, palliative methods for tuberculosis treatment were developed, including extrapleural pneumothorax and other successful collapse and resection therapy methods. Epidemiological tracing of tuberculosis also played an important role in fighting this disease among Slovenes. The introduction of the Tuberculosis Register at Golnik, dispensary work, hospital treatment, mass vaccination, and fluorography screenings led to a significant decrease in tuberculosis. In mid-1960's, tuberculosis was under total control in Slovenia and sin ce 2005 non-selective vaccination of newborns is no longer obligatory. Nevertheless, tuberculosis still is and remains a disease of the poor, although it is also found in developed countries, where many people are infected with human immunodeficiency virus (HIV) and tuberculosis does not respond to routine treatment with antitubercular agents. Despite exceptional developments in the field of medicine, tuberculosis thus promises no rest for experts in the foreseeable future.
Keywords: tuberkuloza; zgodovina medicine; javno zdravje; sanatoriji; cepljenje